The Effect of Recreational Awareness on Attitude Towards Sport Tourism - Yeşim Araboğa; Serkan Ak (Research in Sport Education and Sciences)
This study examined the impact of recreational awareness levels among undergraduate students in the recreation department on attitudes towards sports tourism. The study involved constructing a model to evaluate the influence of recreational awareness sub-dimensions on the sub-dimensions of attitude towards sports tourism. A total of 209 undergraduate students enrolled in the Recreation Department of XXX University participated in the study. The participants completed the personal information form, the Recreational Awareness Scale and the Scale of Attitude Towards Sports Tourism Scale. The research data were analyzed using SPSS 22 and Smart PLS 4 software. Partial least squares structural equation modeling (PLS-SEM) was the preferred method of analysis. In this context, the measurement and structural models were evaluated. The findings indicated that students in the recreation department demonstrated high recreational awareness and positive attitudes towards sports tourism. The results for testing the hypotheses demonstrate that all dimensions of recreational awareness significantly and positively impact the economic contribution dimension of attitude towards sports tourism. Conversely, recreational awareness’s social/success and self-improvement dimensions positively influence the job opportunities dimension of attitude towards sports tourism. Moreover, while the personal contribution dimension of attitude towards sports tourism is significantly influenced solely by the self-improvement dimension of recreational awareness, the organization dimension of attitude towards sports tourism is affected only by the social/success dimension of recreational awareness.